Post-traumatic Growth: Longitudinal Study on Battered Women in Close Relationships after Both They and Their Partners Undergo Therapy - Dyjakon, Dorota (Journal of interpersonal violence, 2022)
Violence in intimate relationships is a major problem worldwide. Many women, despite having experienced violence from a partner, decide to remain in a relationship with the perpetrator. A special premise for such a decision is that the abusive partner undertakes therapy that serves to build security in the family. An important indicator of dealing with violence is post-traumatic growth (PTG), a concept introduced by Calhoun and Tedeschi (1998) to describe positive changes as a result of traumatic experiences. The purpose of the research was to assess PTG changes in the course of relationships in which the woman had experienced violence from her partner, but both her partner and she had undertaken therapy and changed their behavior (N = 48). The conducted research used a demographic survey and two questionnaires: The Polish version of the Impact Event Scale-Revised (IES-R, Weiss, Marmara prepared by Juczy?ski and Ogi?ska-Bulik [2009]) examining three dimensions of trauma (intrusion, hyperarousal, and avoidance) and the Post-traumatic Growth Inventory (Tedeschi Polish version prepared by Ogi?ska-Bulik & Juczy?ski [2010]). The studies showed that over a period of one and half years, significant changes in PTG had taken place. Reportedly, changes in self-perception and changes in relating to others have decreased, while appreciation of life increased but spiritual life remained the same. The research also allowed us to distinguish several groups of corelates in changes in individual PTG categories. The studies also indicate that building a close relationship with the person who caused the harm can limit the victim?s PTG.